2013
DOI: 10.1021/ja408354s
|View full text |Cite
|
Sign up to set email alerts
|

Fast, Label-Free Force Spectroscopy of Histone–DNA Interactions in Individual Nucleosomes Using Nanopores

Abstract: Herein we report a novel approach for fast, label-free probing of DNA-histone interactions in individual nucleosomes. We use solid-state nanopores to unravel individual DNA/histone complexes for the first time, and find that the unraveling time depends on the applied electrophoretic force, and our results are in line with previous studies that employ optical tweezers. Our approach for studying nucleosomal interactions can greatly accelerate our understanding of fundamental mechanisms by which transcription, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 32 publications
4
52
0
1
Order By: Relevance
“…12 Furthermore, nanopores may be exploited to characterize and separate synthetic macromolecules. The various charged macromolecules used in the health care and materials industries typically start out highly polydisperse.…”
Section: Beyond Sequencingmentioning
confidence: 99%
“…12 Furthermore, nanopores may be exploited to characterize and separate synthetic macromolecules. The various charged macromolecules used in the health care and materials industries typically start out highly polydisperse.…”
Section: Beyond Sequencingmentioning
confidence: 99%
“…[37] Wanunu and co-workers reported an approach for the fast, label-free probing of DNA-histone interactions in individual nucleosomes by unraveling the DNA-histone complexes with an SSnanopore. [38] Yu et al demonstrated the identification of zinc finger binding site within ad sDNAt oas ingle protein resolution using alow noise solid-state nanopore. [39] Similarly, Bashir and co-workers used methyl-binding proteins (MBPs) to selectively label the methylated DNAa nd accomplished the detection of methylation in dsDNAf ragments.…”
Section: Methodsmentioning
confidence: 99%
“…Different kinds of proteins, [97,98] DNA-protein complexes, [99,100] biomarkers, enzyme flexibilities, [101] and biochemical processes [5] have been widely studied through the electrical signals obtained from nanopores. Now, with the help of high-sensitivity and specific optical signals, more detailed research on those biochemical processes and molecules in suit can be conducted.…”
Section: Identification Of Complexes and Biochemical Processes At Thementioning
confidence: 99%